1998
DOI: 10.1046/j.1365-2265.1998.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

L‐Arginine and insulin‐tolerance tests in the diagnosis of adult growth hormone deficiency: influence of confounding factors

Abstract: Since provocative GH responses are influenced by external factors, conditions should be standardized to optimize the reproductibility and specificity of the tests. Furthermore the higher specificity of the insulin-tolerance test as compared to the arginine stimulation test was confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…The CV of the ITT is comparable to that found in the GHRHpyridostigmine test (13), and the CVs between GH response to test one and two comparable to those found in the GHRH-arginine test in different age groups (14). We have previously demonstrated that external factors such as physical activity prior to testing may confound the test result (15), and therefore the subjects in our study were admitted to hospital the night before testing. Pre-testing factors may thus explain some of the disagreement in peak GH variability in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…The CV of the ITT is comparable to that found in the GHRHpyridostigmine test (13), and the CVs between GH response to test one and two comparable to those found in the GHRH-arginine test in different age groups (14). We have previously demonstrated that external factors such as physical activity prior to testing may confound the test result (15), and therefore the subjects in our study were admitted to hospital the night before testing. Pre-testing factors may thus explain some of the disagreement in peak GH variability in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although the combined ARG plus GHRH test has been proposed to be the best alternative to the ITT with a peak GH cut-point of 9 g/liter (3,5), this test has been reported to be performed in fewer than 1% of patients in the United States (4). While the response to multiple pharmacologic agents in healthy adults has been evaluated in several studies (6 -12), comparison of diagnostic stimulation tests in patients with hypothalamic-pituitary disease has been limited to two or three tests in prior studies (5,(13)(14)(15)(16). Drawbacks of earlier studies included a lack of control subjects or matching control subjects to hypopituitary patients by age and sex alone.…”
Section: G H Deficiency (Ghd) In Adults Is Now a Well-recog-mentioning
confidence: 99%
“…Although there was no gender difference in the GH response to the ITT, glucagon, or clonidine, women had a significantly higher peak response to arginine, thought to be due to an enhancing effect of oestrogens [27]. The arginine stimulation test has been shown to have a significantly lower specificity than the ITT [28]. …”
Section: Assessment Of Ghd In Adultsmentioning
confidence: 99%